Mechanically Robust, Negative‐Swelling, Mussel‐Inspired Tissue Adhesives. Issue 5 (23rd November 2012) - Barrett, Devin G.; Bushnell, Grace G.; Messersmith, Phillip B.
Abstract Most synthetic polymer hydrogel tissue adhesives and sealants swell considerably in physiologic conditions, which can result in mechanical weakening and adverse medical complications. This paper describes the synthesis and characterization of mechanically tough zero‐ or negative‐swelling mussel‐inspired surgical adhesives based on catechol‐modified amphiphilic poly(propylene oxide)‐poly(ethylene oxide) block copolymers. The formation, swelling, bulk mechanical, and tissue adhesive properties of the resulting thermosensitive gels were characterized. Catechol oxidation at or below room temperature rapidly resulted in a chemically cross‐linked network, with subsequent warming to physiological temperature inducing a thermal hydrophobic transition in the PPO domains and providing a mechanism for volumetric reduction and mechanical toughening. The described approach can be easily adapted for other thermally sensitive block copolymers and cross‐linking strategies, representing a general approach that can be employed to control swelling and enhance mechanical properties of polymer hydrogels used in a medical context.